Successful Fitting of a Complete Maxillary Denture in a Patient with Severe Alzheimer’s Disease Complicated by Oral Dyskinesia - Hiromitsu Morita; Akie Hashimoto; Ryosuke Inoue; Shohei Yoshimoto; Masahiro Yoneda; Takao Hirofuji (Case Reports in Dentistry)
There is an increasing population of elderly patients suffering from Alzheimer’s disease (AD), the most common form of dementia. In dentistry, a critical problem associated with these patients is the use of a new denture, as AD patients often refuse dental management and are disturbed by minor changes in their oral environment. Some AD patients have further complications associated with oral dyskinesia, a movement disorder that can make dental management difficult, including the stability of a complete denture. In this case, we successfully fitted a complete maxillary denture using modified bilateral balanced occlusion after multiple tooth extractions under intravenous sedation in a 66-year-old woman with severe AD complicated by oral dyskinesia. Following treatment, her appetite and food intake greatly improved. Providing a well-fitting complete denture applied by modified bilateral balanced occlusion, which removes lateral interference using zero-degree artificial teeth for movement disorder of the jaw in patients with severe AD complicated by oral dyskinesia, helps improve oral function.